Case report: Persistent truncus arteriosus with intact ventricular septum and other cardiovascular malformations in a calf - Eroksuz, H.; Yilmaz, S.; Eroksuz, Y.; Cevik, A.; Soylu, S.; Karabulut, B. (Ecole Nationale Veterinaire Toulouse, 2015)
A 3-day old, male Holstein calf presented for necropsy with a history of respiratory distress, recumbency and failure to suckle since birth. Postmortem examination revealed the absence of an aorta and a single artery arising from the right ventricle that became the pulmonary trunk, which branched into the main pulmonary artery and rise to two pulmonary arteries (type-1 persistent truncus arteriosus). Other related findings included intact ventricular septum, left ventricular hypoplasia, left coronary artery originating from brachiocephalic trunk, absence of right coronary artery and patent foramen ovale. Microscopically, there was moderate, diffuse subendocardial fibrosis, myocardial degeneration, necrosis and multifocal mononuclear cell infiltrations, which were most prominent in the left ventricle wall. Additionally there was marked medial thickening of arterial and arteriolar walls in the lungs. Pulmonary parenchymal changes included moderate edema, vascular and interstitial congestion, hemosiderin laden macrophages and diffuse suppurative pneumonia. Consequently, the concurrence of type-1 persistent truncus arteriosus, left ventricular hypoplasia, single right coronary artery and anomalous origin of the right coronary artery was unusual in many respects and contributed to this calf's failure to thrive and early death.
Keywords: bovine; left ventricular hypoplasia; persistent truncus arteriosus